Analisis Faktor-faktor yang Mempengaruhi Cadangan Devisa - Wardani Umi Maesyaroh; Kundhani, Eranus Yoga (Jurnal Ilmu Ekonomi JIE, 2024)
Foreign exchange reserves are assets in the form of foreign currency a country holds and are used in international trade. In addition to being used for international transactions, foreign exchange reserves also play a role in maintaining the stability of the country's economy and financial system. Therefore, this research aims to analyze the factors that influence foreign exchange reserves in the short and long term, such as exports, foreign direct investment (FDI), foreign debt, and interest rates. This research uses the Error Correction Model (ECM) method with data from 1986 to 2021. The research results show that exports and foreign debt positively and significantly impact foreign exchange reserves in the short and long term. Foreign Direct Investment (FDI) has a negative and significant impact on foreign exchange reserves in the short term, but it does not have an effect in the long term. Meanwhile, interest rates do not influence foreign exchange reserves in the short and long term. Overall, these variables contribute to controlling foreign exchange reserves.